Fenomena Eksploitasi Agraris Oleh Kaum Kapital Domestik - Peribadi . (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2013)
ABSTRACT The objectives of this research are to identify and to prove the phenomena of domestic capital that directly or not apply capitalism approach, or agrarian imperialism toward social economic life of farmer community in the village. This research applies field research method by focusing to participatory development approach. The data were collected by applying participatory rural appraisal (PRA), focus groups discussion, FGD), and in depth interview. The results showed that the process of exploitation of the wilderness mountain has been transformed into several villages and even into some areas have formed mountain villages, so fatal to rural residents located in the lower area. This subject increasingly worried about the surrounding communities, because the exploitation was not only done by the people who categorize as greedy of land. Not only the farmer who continually adding plantation areas, but also unscrupulous local elite who play role in government bureaucracy. Key words: exploitation, capital actors and estates